Analysis of Causes and Treatment of Leaks Pipe in the Process of Loading and Discharging Liquid Bulk Commodities Types of Fuel - Case Study at Tanjung Wangi Port - Rindraputra, Althaf Maheswara; Setiono, Benny Agus; Saputra, Toto Dwijaya (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2024)
Analysis of Causes and Treatment of Leaks Pipe in the Process of Loading and Discharging Liquid Bulk Commodities Types of Fuel: Case Study at Tanjung Wangi Port. Pipe leaks in the process of loading and discharging liquid bulk commodities, types of fuel, at Tanjung Wangi Port are serious problem that needs to be handled quickly and effectively. Pipe leaks can cause significant financial losses, environmental damage and danger to public health. This research aims to analyze the causes of pipe leaks during the loading and unloading process of liquid bulk commodities such as fuel oil at Tanjung Wangi port and identify effective solutions for handling these leaks. The research was carried out using qualitative analysis methods. The research results show that the causes of pipe leaks can come from human factors, such as errors in the loading and unloading process or pipe operation. Apart from that, technical factors such as wear and corrosion on pipes can also cause leaks. To handle pipe leaks, this research recommends implementing preventive measures which include routine maintenance, use of corrosion-resistant pipe materials, as well as high training and awareness for officers involved in the loading and unloading process. Apart from that, this research also suggests the use of sophisticated leak detection technology to detect leaks early and reduce the impact they cause.